Ausbaustrecke Emmerich - Oberhausen. Fortsetzung der Betuwe-Route in Deutschland. - Reineke, Friederike (Deutscher Verkehrs-Verlag, 2004)
Die Strecke zwischen der deutsch-niederländischen Grenze über Emmerich nach Oberhausen gewinnt mit der für 2007 geplanten Fertigstellung der niederländischen Betuwe-Route vom Hafen Rotterdam nach Zevenaar erheblich an Bedeutung. Eine Erhöhung der Leistungsfähigkeit der vorhandenen Strecke wird in Deutschland von vielen Seiten gefordert. Große Anteile der zusätzlichen Güterverkehre von der niederländischen Grenze über Oberhausen haben zum Einen Richtung Süden die Rheinschiene sowie den Rangierbahnhof Köln-Gremberg und zum Anderen den Südosten Deutschlands sowie den Rangierbahnhof Hagen-Vorhalle zum Ziel. Die Pläne für die Strecke in diesem Zusammenhang stellt der Artikel dar. difu

The Betuwe Route - which is used for freight traffic only - is to be completely rebuilt. Freight trains are planned to operate between the port of Rotterdam and he German border along a double track route. On the German side, it is intended to extend the Betuwe Route between Oberhausen and Emmerich. The intention to increase the route's capacity by way of shortening service intervals and providing for three tracks, has been incorporated into the BVWP 2004 as a matter of priority. As per an agreement between the DB, the Federal Government and the Land of North-Rhine Westphalia, this expansion is to be carried out in stages. To start with, the DB will prepare the necessary expansion plans while, in certain areas, the land can begin to adopt noise prevention measures by using its own financial resources. During the third stage, the DB will adopt a shorter train service interval pattern and initiate the expansion to a three-track system for which plans are being formulated at the present time. difu
Keywords: Verkehr; Eisenbahn; Güterverkehr; Schienengüterverkehr; Streckenführung; Verkehrswegeausbau; Ausbaustrecke; Verkehrsbedeutung; Güterverkehrsmarkt; Grenzüberschreitender Verkehr